2022
DOI: 10.1002/eom2.12292
|View full text |Cite
|
Sign up to set email alerts
|

Dopant‐free passivating contacts for crystalline silicon solar cells: Progress and prospects

Abstract: The evolution of the contact scheme has driven the technology revolution of crystalline silicon (c-Si) solar cells. The state-of-the-art high-efficiency c-Si solar cells such as silicon heterojunction (SHJ) and tunnel oxide passivated contact (TOPCon) solar cells are featured with passivating contacts based on doped Si thin films, which induce parasitic optical absorption loss and require capitalintensive deposition processes involving flammable and toxic gasses. A promising solution to tackle this problem is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 275 publications
0
19
0
Order By: Relevance
“…Reproduced with permission. [ 111 ] Copyright 2022, Wiley‐VCH. c) Bandgap diagrams and work function positions (dashed lines) of different TCOs, CBMs, TMOs, and FCMs with the c‐Si energy band edges (gray bar) as a reference.…”
Section: Characterization Of Dfpc Materials With Key Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…Reproduced with permission. [ 111 ] Copyright 2022, Wiley‐VCH. c) Bandgap diagrams and work function positions (dashed lines) of different TCOs, CBMs, TMOs, and FCMs with the c‐Si energy band edges (gray bar) as a reference.…”
Section: Characterization Of Dfpc Materials With Key Parametersmentioning
confidence: 99%
“…DFPC materials must be transparent to allow light to pass through and be absorbed by the c-Si. Therefore, transparent [111] Copyright 2022, Wiley-VCH. c) Bandgap diagrams and work function positions (dashed lines) of different TCOs, CBMs, TMOs, and FCMs with the c-Si energy band edges (gray bar) as a reference.…”
Section: Optical Properties: Optical Transmittance With Figure Of Meritmentioning
confidence: 99%
See 2 more Smart Citations
“…[16,17] Concurrently, even though p-type oxides (Cu 2 O, NiO) were expected to work well as hole-selective contacts, their practical performance is often found insufficient as compared to competing n-type metal oxides due to their low hole conductivity and poor surface passivation. [18][19][20][21][22] Indeed, Pramod et al reported 3.9% efficiency in the device with sputtered Cu 2 O contacts. [18] Further, 5.48% efficiency was reached by Kurias et al using borondoped Cu 2 O contacts.…”
Section: Introductionmentioning
confidence: 99%